(+/-)-1,2-Bis(N '-benzoylthioureido)cyclohexane - Jumal, J; Ibrahim, AR; Yamin, BM (Wiley-Blackwell, 2024)
In the title compound, C22H24N4O2S2, the two thiourea segments of the side-arm groups are inclined at a dihedral angle of 73.09 (9)degrees. The central cyclohexane bridge adopts a chair conformation. The molecule is stabilized by N-H center dot center dot center dot O intramolecular hydrogen bonds forming S(6) rings, and N-H center dot center dot center dot O and N-H center dot center dot center dot S intermolecular hydrogen bonds forming infinite chains developing parallel to the b axis.